Analysis of Tubular Linear Motors for Different Shapes of Magnets - Abdalla, I.I. (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper presents the analysis of tubular linear motors for different shapes of magnets. The appropriate option for refrigeration applications is the single-phase tubular permanent magnet linear motor (TPMLM), which provides high efficiency, high thrust force, and low cogging force. Three design variants of TPMLMs with moving magnet and quasi-Halbach magnetization have been proposed, and their finite-element analysis (FEA) models have been established. Accordingly, analytical methods using Fourier series and Maxwell's equations have been created for the three proposed designs, and the results have been compared. It is found that the results from the analytical method are in good agreement with the FEA results. Â© 2013 IEEE.